Efficacy of herbicide – urea tank mixing for weed control in wet seeded rice - Reddy, Thumu Venkateswara; Menon, Meera V.; S., Anitha; George, Daly (Journal of Tropical Agriculture, 2021)
Tank mixing of herbicides with urea is a common practice among rice farmers, done to enhance herbicidal effect and to save labour costs. Field experiments were conducted in 2019-20 and 2020-21 in Alappad Kole in Thrissur, Kerala to evaluate the effect of tank mixing of commonly used herbicides with 1% urea on weed control efficiency and yield of wet seeded rice. Six herbicides, viz., cyhalofop butyl (0.08 kg/ha), cyhalofop butyl + penoxsulam (0.15 kg/ha), bispyribac sodium (0.025 kg/ha), fenoxaprop-p-ethyl (0.06 kg/ha), carfentrazone ethyl (0.02 kg/ha) and chlorimuron ethyl + metsulfuron methyl (0.004 kg/ha) were applied with and without urea mixing, in a Randomized Block Design with three replications. A hand weeded control and unweeded control were also included for comparison. The treatments were applied 15 to 20 days after sowing. At 45 to 50 days after sowing, all the herbicide applied plots were hand weeded to remove all weeds. Results indicated that mixing urea with bispyribac sodium and cyhalofop butyl + penoxsulam were superior to application of these herbicides without urea mixing in reducing weed growth and increasing rice grain yields. Pooled data on weed dry weight at 15 days after herbicide application revealed that mixing with urea could enhance weed control efficiencies of bispyribac sodium and cyhalofop butyl + penoxsulam by 17.5 per cent and 14.85 per cent respectively as compared to their application without urea. Although the highest yield was obtained with hand weeded control (5.13 t/ha), tank mixing with urea resulted in increases in grain yield to the tune of 17.52 per cent on application of bispyribac sodium (5.03 t/ha) and 18.75 per cent on application of cyhalofop butyl + penoxsulam (4.94 t/ha) as compared to their application without urea mixing.